Pendidikan Kesehatan dan Pengobatan Sebagai Preventif dan Kuratif Menuju Masyarakat Sehat di Desa Pedawang Kabupaten Pekalongan - Irnawati, Irnawati; Kamalah, Aisyah Dzil (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Health education and medication activities have apurpose to make the community in the village ofPedawang have proficiency in: (1) increase knowledge;knowledge(2) increase awareness of the disease; (3) increaseawareness for treatment to health service..service. The targetaudience of these activities are community in the villageof Pedawang throughout Pekalongan District.DiThisactivity was precededeceded by conducting needs analysisthrough interviews and surveys of community healthproblem. Implementation of activities carried out byhealth education, medication, and blood test.test Forms ofactivity are designed using health h education strategiesto ensure participants’ knowledge in treatment diseaseand preventing disease can be mastereded well.